Smart Money Moves: The Role of Financial Literacy & Inclusion in Boosting SME Performance in Indonesia - Ningsih, Ni Luh Anik Puspa; Firdaus, Muhammad Yusfi; Putra, I Made Wianto; Putra, Ida Bagus Udayana; Surasmi, Ida Ayu; Ekayani, Ni Nengah Seri (Oeconomica Jadertina, 2026)
More than 60% of Indonesia's GDP comes from Micro, Small, and Medium-Sized Enterprises (MSMEs), which also employ a sizable percentage of the labor force across a range of industries. But even with their significant contribution, a lot of MSMEs struggle with access to formal financial services and financial management. The primary barriers to their expansion and sustainability are low financial literacy and restricted financial inclusion. The management and financial performance of MSMEs are hampered by low financial inclusion and financial literacy. Through financial management practices, this study seeks to examine how financial inclusion and financial literacy affect the financial performance of MSMEs in West Nusa Tenggara (NTB). A quantitative approach using the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique is the study methodology employed. A survey of 100 MSMEs in NTB was used to gather data. The findings demonstrated that financial management behavior is positively and significantly impacted by financial inclusion and financial literacy. Financial performance is positively and significantly impacted by financial management practices and financial inclusion. However, financial performance is significantly and negatively impacted by financial literacy. Furthermore, the relationship is mediated by financial management practices.
Keywords: Financial Literacy; Financial Inclusion; Financial Management Behavior; Financial Performance; MSMEs